CASE REPORT: THE POSSIBILITY OF SPECIFIC THERAPY OPTIMIZATION BY SWITCHING FROM BOSENTAN TO MACITENTAN IN A PATIENT WITH CONGENITAL HEART DISEASE AND EISENMENGER SYNDROME - S. Ye. Gratsianakaya; O. A. Arkhipova; A. I. Davydov; T. V. Martynyuk; N. A. Ananicheva; O. S. Belkorey; I. Ye. Chazova (Евразийский Кардиологический Журнал)
A patient with pulmonary arterial hypertension (PAH) associated with congenital heart disease (ventricular septal defect) and Eisenmenger syndrome was started on an endothelin receptor antagonist bosentan. With treatment, the patient's condition had been stable, however, by the second year, worsening shortness of breath, reduced exercise tolerance and an increase of the right heart were noted. Bosentan was switched to macitentan. After a year of this pathogenetic therapy, an improvement in functional status was registered. Moreover, while on macitentan, the patient has successfully undergone a gynecological surgical procedure under general anesthesia.